Seeking Justice in an Energy Sacrifice Zone - Maldonado, Julie Koppel, author.
1 online resource
Keywords: "Seeking Justice in an Energy Sacrifice Zone is an ethnographic examination of the lived experience of rapid environmental change in coastal Louisiana, USA. Writing from a political ecology perspective, Maldonado explores the effects of changes to localized climate and ecology on the Isle de Jean Charles, Grand Caillou/Dulac, and Pointe-au-Chien Indian Tribes. Focusing in particular on wide ranging displacement effects, she argues that changes to climate and ecology should not be viewed in isolation as just physical processes but as part of wider socio-political contexts. Seeking Justice in an Energy Sacrifice Zone is useful reading for students of environmental anthropology, as well as those taking other environmental and socio-political courses."--Provided by publisher.